"If you wanna make the world a better place": Factors influencing the effect of songs with prosocial lyrics. (July 2019) - Ruth, Nicolas
Although there has been an increase in research considering the positive effects of music with prosocial lyrics on people's behavior, little is known about the process by which this happens or about the factors that influence the effect of listening to songs with prosocial content. This study focused on the interaction between attention level and familiarity, two factors that, to some degree, determine the effect of this kind of music. Based on the general learning model, the reciprocal feedback model of music perception, and the elaboration likelihood model, an online experiment ( n = 220) was conducted to test how people listening attentively to familiar or unfamiliar music with prosocial lyrics are affected, in comparison with those listening inattentively. The results yielded a significant interaction effect between attention and familiarity on prosocial behavior, indicating that only familiar songs with prosocial lyrics affect inattentive listeners, whereas attentive listeners are affected similarly by familiar and unfamiliar songs. Effects on emotions and an indirect effect of familiarity on prosocial behavior via activated pre-knowledge and positive emotions were also found. The results are discussed regarding their role in understanding the music reception process and their meaning for listeners' prosocial behavior.